Herança genética e associação de marcadores microssatélites à resistência à Liriomyza sativae em meloeiro - Leitão, Liliana Rocivalda Gomes (2018)
The melon (Cucumis melo L.) is a cucurbit crop with worldwide prominence. In Brazil, it has relevant socioeconomic importance in the Northeast region. The leafminer, Liriomyza spp. (Diptera: Agromyzidae), is the main pest of the crop, causing serious damages to the plant and, consequently, reducing the production and the quality of the fruits. The use of resistant genotypes is the most efficient and sustainable method of insect control, however, few sources of resistance to this insect have been identified in melon germplasm. The elucidation of genetic inheritance and the use of molecular markers are tools that aid in the introgression of leafminer resistance in melon hybrids. Considering two new sources of resistance to leafminer in melon, the objective was to elucidate the genetic control in line A915.34.01.08 and to identify microsatellite markers (SSR) associated with resistance in line A56.10.04. For the study of inheritance, each lineage (P1), resistant by antibiosis, was crossed with a susceptible lineage (P2), forming their respective hybrid (F1), which were self-pollinated and backcrossed with both parents obtaining the progeny (F2) and backcrosses (RC1 and RC2), respectively. The trials were conducted in a greenhouse and under field conditions, using natural populations of L. sativae, using a completely randomized design, with six treatments (P1, P2, F1, F2, RC1, RC2), different number of plants per replications, totaling 300 plants each experiment. The number of mines in leaves was counted and larval development were quantified, in which the plants were classified as resistant (without pupal development) or susceptible (at least one pupal development). Regarding the association of SSR markers with the resistance, a total of 328 primers were evaluated for the polymorphism in the P1, P2 and F1 generations and, later, the F2 generation was genotyped with the markers identified as polymorphic. Generation analysis demonstrated that four genes control leafminer resistance in line A915.34.01.08. Two SSR markers, CM321 and CM333, are associated with the L. sativae resistance gene in line A56.10.04. Therefore, the A915.34.01.08 lineage has an oligogenic inheritance, and can be used for the introgression of resistance in elite lines of melon, and the markers CM321 and CM333 are linked to the Ls gene, being able to be used in the selection assisted to the leafminer in the melon breeding program.